2020
DOI: 10.1093/cid/ciaa1422
|View full text |Cite
|
Sign up to set email alerts
|

Severe Acute Respiratory Syndrome Coronavirus 2 Spreads to Lymph Nodes and Strongly Expands CD4+ Effector Memory RA Cells in a Patient With Mild Coronavirus Disease 2019

Abstract: A woman with mild Covid-19 developed cervical adenopathy, being diagnosed of Epstein−Barr virus infectious mononucleosis. After a FNAP we demonstrate that SARS-CoV-2 is found in lymph nodes (LNs) even in mild disease along with a strong expansion of terminally differentiated effector memory CD4+T-cells , a cell population that is practically absent in LN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 10 publications
1
5
0
2
Order By: Relevance
“…However, we have found no reports regarding the onset of tonsillitis, such as tonsillar redness and pus coating, in COVID-19 patients, except for a single case report of co-infection with both EBV and COVID-19 [15] . In addition, if both fine-needle aspiration cytology and a subsequent LAMP examination had been conducted on the specimens from the swollen cervical lymph nodes in this case similarly as Roldán-Santiago et al [17] reported, then the cause-effect relationship between the IM and SARS-CoV-2 might have been confirmed.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…However, we have found no reports regarding the onset of tonsillitis, such as tonsillar redness and pus coating, in COVID-19 patients, except for a single case report of co-infection with both EBV and COVID-19 [15] . In addition, if both fine-needle aspiration cytology and a subsequent LAMP examination had been conducted on the specimens from the swollen cervical lymph nodes in this case similarly as Roldán-Santiago et al [17] reported, then the cause-effect relationship between the IM and SARS-CoV-2 might have been confirmed.…”
Section: Discussionsupporting
confidence: 58%
“…In IM caused by an initial EBV infection, massive proliferation of T lymphocytes activated by EBV-infected B cells is considered to cause the enlargement of the tonsils and cervical lymph nodes. Roldán-Santiago et al [17] reported that SARS-CoV-2 was detected in the cervical lymph nodes by fine-needle aspiration cytology in three COVID-19 cases showing lymphadenopathy. SARS-CoV-2 has been reported to infect various types of cells expressing ACE2 via the viral S protein, since ACE2 is ubiquitously expressed in almost all cells.…”
Section: Discussionmentioning
confidence: 99%
“…Radiographic analysis has concluded that lymphadenopathies are characteristically absent in most SARS-COV-2 patients who were investigated using CT, which seems rare. 7 FNAC is the most preferable diagnostic tool to detect CLA. Our case was idiosyncratic as the patient was symptomatic with only fever, right sided neck pain and odynophagia and these findings were consistent with MIS-C.…”
Section: Discussionmentioning
confidence: 99%
“…2 CLA is one of the clinical features of MIS-C, that had only seen in 6% patients who were hospitalized for COVID-19. 7 Henceforth we will describe the first case of MIS-C post-COVID-19 infection with CLA in India was reported in a young adult.…”
Section: Introductionmentioning
confidence: 96%
“… 3 Also, there is still a concern of infected lymphoid cells left in the donated intestine as active replicating SARS‐CoV‐2 has been found in intestinal tract. 4 …”
mentioning
confidence: 99%